In silico study: molecular docking of SARS-Cov-2 endoribonuclease on active compounds of Gmelina arborea Roxb. bark - Shobiroh Nuur'Alimah; Agnia Nurul Jannati; Laksmi Ambarsari; Syamsul Falah (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Infection by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) triggers COVID-19 disease of the respiratory tract similar to pneumonia. The virus encodes four structural proteins and 16 non-structural proteins (nsp), one of which includes nsp15 or endoribonuclease (NendoU). NendoU plays an important role in viral replication and transcription and reduces the stimulation of immune cell responses. Active compounds in Gmelina arborea Roxb. bark have antioxidant properties that can inhibit the NendoU activity of SARS-CoV-2. This study aims to analyze the potential of compounds from Gmelina arborea Roxb. bark in inhibiting SARS-CoV-2 NendoU within in silico using the YASARA structure application. Balnophonin is the best test ligand based on binding ΔG value, dissociation constant (Kd), prediction of physicochemical characteristics, pharmacokinetics, and toxicity. Therefore, balanophonin can be developed as an effective alternative drug to inhibit SARS CoV-2 NendoU.